Pengembangan Permainan Ludo Kimia sebagai Media Pembelajaran pada Materi Termokimia - Putri Alia; Iswendi Iswendi (Universitas Negeri Padang, 2021)
ABSTRACTThe chemical ludo game is a learning media that is useful as an exercise to strengthen the stabilization of students' thermochemical concepts. This study aims to develop the ludo-chemistry game media against thermochemical material and determine the level of validity of the chemical ludo-play media. This type of research is a Educational Desaian Research with a PLomp development model. The development of the ludo chemistry game is limited to the expert review stage. Data were collected using a validation questionnaire. Validation was carried out by four validators, and for the 0ne to one test, it was carried out by three students. The data analysis technique used Aikens V. The results of the media validation test had a V value of 0.85 with the valid category. Thus, the chemical ludo game is said to be valid as a learning medium for class XI thermochemical material.Keywords: Ludo Chemical, Learning Media, Thermochemical, Plomp Aikens V.ABSTRAKPermainan Ludo Kimia merupakan media pembelajaran yang berguna sebagai latihan untuk pemantapan konsep Termokimia peserta didik. Penelitian ini bertujuan untuk mengembangkan media permainan ludo kimia terhadap materi Termokimia dan menentukan tingkat validitas dari media. Jenis penelitian ini adalah penelitian Educational Desaian Research dengan model pengembangan plomp. Pengembangan permainan ludo kimia dibatasi sampai tahap expert review. Pengambilan data dilakukan dengan menggunakan angket validasi. Validasi dilakukan oleh empat orang validator, dan untuk uji one to one dilakukan oleh tiga orang peserta didik. Teknik analisa data menggunakan formula Aikens V. hasil uji validasi media memilik nilai V sebesar 0,85 dengan kategori valid. Dengan demikian permainan ludo kimia dikatakan valid sebagai media pembelajaran untuk materi Termokimia kelas XI.Kata Kunci: Permainan Ludo Kimia, Media Pembelajaran, Termokimia, Plomp, Aikens V